2019
DOI: 10.29130/dubited.539930
|View full text |Cite
|
Sign up to set email alerts
|

Cr ve Ni İlavesinin Sade Karbonlu Çeliğin Mekanik Özelliklerine Etkisi

Abstract: In this study, the effect of Cr-Ni addition on the mechanical properties of plain carbon steel was investigated. For this purpose, Cr-Ni (wt. % 0.5-3) was added to the matrix containing 0.5 C with powder metallurgy method. The tensile test, micro hardness measurement and microstructure analysis were performed to investigate the effect of the additions on the mechanical properties. As a result, it was determined that the added alloying elements increased the mechanical properties, but the mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The critical parameter for hardening is the Cr/C ratio, and the higher the ratio, the higher the hardenability. Some studies 21 showed that Cr increased the effect of precipitation hardening in steels. Erden and Demirtaş 21 investigated the effect of Cr-Ni addition on plain carbon steel’s mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical parameter for hardening is the Cr/C ratio, and the higher the ratio, the higher the hardenability. Some studies 21 showed that Cr increased the effect of precipitation hardening in steels. Erden and Demirtaş 21 investigated the effect of Cr-Ni addition on plain carbon steel’s mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies 21 showed that Cr increased the effect of precipitation hardening in steels. Erden and Demirtaş 21 investigated the effect of Cr-Ni addition on plain carbon steel’s mechanical properties. As a result, it was determined that the addition of alloying elements increased the mechanical properties, but the mechanical properties decreased with the amount of alloying elements increasing after 1% wt.…”
Section: Introductionmentioning
confidence: 99%
“…Demirtaş and Erden [9] produced Cr-Ni steel with the PM method. In this study, the effects of Cr-Ni addition on the tensile strength properties of powder metallurgy plain carbon steel were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Demirtaşand Erden investigated the effect of the addition of Cr-Ni (0.5-3% by weight) on the mechanical properties to the matrix containing 0.5 C by powder metallurgy method. 17 Their results showed that the addition of the Cr and Ni alloying elements has increased the tensile strength and hardness. Kandavel et al investigated the effects of titanium (Ti) and tungsten (W) addition on tribological behavior of (PM Fe-1%C steel using artificial neural network (ANN).…”
Section: Introductionmentioning
confidence: 99%